Evaluasi Kecernaan In Sacco Beberapa Pakan Serat yang Berasal dari Limbah Pertanian dengan Amoniasi - Andayani, Jul (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2008)
The aim of this study was to evaluate the effect ammoniated feed from agriculture by products on the in  sacco  dry  matter,  organic  matter  and  crude  protein  digestibilities. This  study  was  assigned  into a completely  randomized  design  (CRD)  with  4  treatments  and  5  replications.  The  treatments  were different types of low quality fibre of agricultural by-products found in Jambi Province; A = ammoniated rice straw with 6 % of urea and 15 % of inoculated rumen digesta, B = ammoniated palm oil fibre with 6% of urea and 15 % of inoculated rumen digesta, C = ammoniated corn peel with 6 % of urea and 15 % of inoculated rumen digesta, D = ammoniated top cane with 6 % of urea and 15 % of inoculated rumen digesta.  Result  of  this  study  showed  that  the  treatments  were  significantly affect (P<0,05) on  the dry matter,  organic  matter  and  crude  protein  degradations.  Ammoniation  significantly  increased degradation  of  feed  compared  with those without  ammoniation. It  is  concluded  that  ammoniation  with urea and addition of rumen digesta increased fibre quality of agricultural by-products. Different of type of ammoniated feed resulted in the difference respond on the nutrient degradation.